Synkinesis in Bell's palsy in a randomised controlled trial. (22nd December 2016) - Bylund, N.; Jensson, D.; Enghag, S.; Berg, T.; Marsk, E.; Hultcrantz, M.; Hadziosmanovic, N.; Rodriguez‐Lorenzo, A.; Jonsson, L.
Abstract : Objectives: To study the development of synkinesis in Bell's palsy. Frequency, severity, gender aspects and predictors were analysed. Design: Data from the randomised controlled Scandinavian Bell's palsy trial including 829 patients. Main outcome measures: Frequency and severity of synkinesis at 12 months were the main outcome measures. Mean Sunnybrook synkinesis scores, voluntary movement scores and composite scores between 6 and 12 months were compared. Results: In 743 patients with a 12‐month follow‐up, synkinesis frequency was 21.3%. There was no gender difference. Synkinesis was moderate to severe in 6.6% of patients. Those with synkinesis at 6 months had a synkinesis score of 4.1 (±2.8sd ), which increased to 4.7 (±3.2) ( P = 0.047) at 12 months ( n = 93). Sunnybrook composite score at 1 month was the best predictor for synkinesis development with receiver operating characteristics and area under the curve (AUC) 0.87. Risk for synkinesis increased with a lower Sunnybrook composite score. Furthermore, at 1 month, symmetry of voluntary movement had higher predictive value for synkinesis than resting symmetry with AUC 0.87 and 0.77, respectively. Gentle eye closure and open‐mouth smile were the only independent significant predictive items (AUC 0.86). Conclusions: Moderate‐to‐severe synkinesis was present in 6.6% of patients. The mean synkinesis score increased between 6 and 12 months, and outcome should therefore be evaluated after at least 12 months. Sunnybrook composite score and symmetry of voluntary movement at 1 month were good predictors for synkinesis.